Case report: A rare case of bilateral Leber’s idiopathic stellate neuroretinitis - He, Wei; Tang, Panli; Lv, Hongbin; Qiao, Lifeng (Frontiers in Medicine, 2024)
Background：Leber’s idiopathic stellate neuroretinitis (LISN) is a rare disease characterized by disc edema, peripapillary and macular hard exudates, and often, the presence of vitreous cells. To enhance clinical understanding of the disease, a retrospective analysis was conducted on a patient diagnosed with LISN at our hospital, and discussions were held regarding its diagnosis and treatment. Methods: We reviewed the medical records of a 26-year-old male patient whose main complaint was a decrease in visual acuity of both eyes for 4 days, which had worsened over the last day. After systemic examination, fundus fluorescein angiography, and indocyanine green angiography, the patient was diagnosed with LISN in both eyes. After treatment with glucocorticoids, the patient's vision showed a significant improvement. Results: Upon admission, the visual acuity of both eyes was: VOD 0.05, VOS 0.25. After 5 days of treatment, the visual acuity of both eyes was: VOD 0.25, VOS 0.4. After 1 month of follow-up, the visual acuity of both eyes was: VOD 0.4, VOS 0.6. After 5 months of follow-up, the patient's vision improved to VOD 0.6, VOS 0.8. Conclusion: The cause of LISN remains unidentified. It is essential to rule out diseases exhibiting similar clinical signs but possessing a clear etiology. The primary treatment approach involves glucocorticoid-based anti-inflammatory therapy, potentially supplemented with antibiotics, antivirals, vasodilators, and traditional Chinese medicine. This disease is usually self-limiting and generally carries a favorable prognosis.